The summer tree - Kay, Guy Gavriel (Kay, Guy Gavriel. Fionavar tapestry (New York, N.Y.), 2001)
Five university students--Kimberly, Dave, Jennifer, Kevin, and Paul--meet a wizard who takes them to the heart of all worlds, Fionavar, where they discover who they were truly meant to be.